Development of caseous calcification of mitral annulus after initiation of hemodialysis therapy. Issue 6 (June 2019) - Usuku, Hiroki; Yamamoto, Eiichiro; Oike, Fumi; Tsunoda, Ryusuke; Nishigami, Kazuhiro; Sakaguchi, Takeshi; Suzuki, Ryusuke; Uekihara, Soichi; Matsui, Hirotaka; Tsujita, Kenichi
Abstract: We here present a 59-year-old man who had undergone peritoneal dialysis (PD) for 7 years and hemodialysis for the following 6 years in the Japanese Red Cross Kumamoto Hospital. Six years after commencing PD, transthoracic echocardiography showed a highly echoic mass with a transverse diameter of almost 15 mm in the posterior mitral leaflet. Because the mass increased from 2 years after initiation of hemodialysis, reaching over 25 mm by 6 years after commencing hemodialysis, tumor resection and mitral valve replacement were performed. When the surface of the mass was incised, white opalescent liquid drained out of the mass and histological examination showed multiple calcified nodules and granulation tissue, resulting in diagnosis of a caseous calcification of mitral annulus. <Learning Objective: Caseous calcification of mitral annulus (CCMA) is usually associated with end-stage renal disease. In the present case, a 59-year-old man had undergone peritoneal dialysis for 7 years, after which he had undergone hemodialysis for 6 years. The development of CCMA was seen after initiation of hemodialysis therapy. Routine echocardiography is useful for early diagnosis of CCMA, especially in patients whose type of dialysis changed from PD to hemodialysis.>